MENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPAS MELALUI PENERAPAN MODEL TEAM GAMES TOURNAMENT - Habi, Sri Yolanda; Munirah, Munirah; Bakari, Aljunaid (DIRASATUL IBTIDAIYAH, 2024)
AbstractThis research aims to find out whether the application of the Times Games Tournament (TGT) model can improve student learning outcomes in science and science learning for class V students at Madrasah Ibtidaiyah Al-Falah Limboto Barat. The Times Games Tournament model is expected to improve student learning outcomes. This research is classroom action research (PTK). The subjects of this research were class V students at MI Al-Falah Limboto Barat. The object of this research is increasing student learning outcomes in science and science learning through the implementation of the Team Games Tournament model in Phase C in Class V of Madrasah Ibtidaiyah Al-Falah Limboto Barat. The treatment given to research subjects was to improve student learning outcomes in science and science learning in phase C in class V using the Times Games Tournament model. The results of this research show that student learning outcomes in cycle 1 were 75% and in cycle II there was an increase of 17% to 92%. The indicator of success in this research is an increase in student learning outcomes, marked by the achievement of the minimum completeness criteria (KKM) with an average completion level of 75% in science learning.Keywords: Team Games Tournamet; Learning outcomes; IPAS.